Korea's Capital Market Promotion Policies: IPOs and Other Supplementary Policy Experiences - Woo Chan Kim (KDI Journal of Economic Policy, 2015)
This paper studies a series of capital market promotion policies Korea pursued over a 30-year period during its development era (1960s - 1980s). The purpose of this paper is twofold. The first purpose is to understand the policy approaches Korea took, and the second is to extract lessons that can benefit policymakers in the developing world, where capital market promotion is an important policy goal. There are two key features of Korea's capital market promotion policies. First, the government was actively involved, sometimes indirectly by giving tax incentives to encourage IPOs. However, in other times, it was directly involved by giving IPO orders and threatening those that did not comply. No stock exchange in a developed country has ever experienced such government involvement. Combined with rapid economic growth, this interventionist approached allowed the Korean stock market to experience phenomenal growth over a short period of time. Second, the capital market promotion policies had multiple objectives. One was to mobilize domestic capital for economic development. Another was to lower firms' debt-to-equity ratios. Most interestingly, however, the Korean government wanted to popularize stock ownership, thereby allowing ordinary Koreans to share in the fruits of economic growth.
Keywords: N25; O16; O20; O53; 330; Capital market promotion; initial public offering; securities deposit and settlement systems; employee stock ownership plan; Korea